Functional Outcomes of Patients with Ankylosed Elbow Managed with Fascia Lata Interposition Arthroplasty and Early Post-operative Active Motion Protocol - Emmanuelle Yap; Raymar Sibonga; Henry Jr Tabinas (Philippine Journal of Orthopaedics)
Background: Interposition arthroplasty is a non-prosthetic-requiring surgery that restores motion in young patients with ankylosed elbows who are not amenable to total elbow arthroplasty, elbow arthrodesis, or resection arthroplasty. This procedure usually requires extensive soft tissue stripping to free the elbow joint, an interposition graft, and post-operative immobilization.